PERBANDINGAN DAYA DUKUNG FONDASI TIANG BOR MENGGUNAKAN METODE REESE & WRIGHT DAN MEYERHOF - Yelvi Yelvi; Muchsin Farid Habibie; Putera Agung Maha Agung (Construction and Material Journal, 2022)
The Serang-Panimbang Toll Road Construction Project is one of the National Strategic Projects (PSN) with a total length of 83,677 km. The main bridge 18, which is one of the projects on the toll road section, has a drill pile foundation for its substructure. The drill pile foundation is a pile foundation that is installed by drilling the ground first, then filling it with reinforcement that has been assembled and cast in concrete. The foundation has a slope that is less than the permitted slope to support the load above it and is built to withstand both vertical and horizontal stresses. This study compared the Reese & Wright method with the Meyerhof method, two bearing capacity estimation techniques. The comparison aims to determine whether the outcomes of the two approaches utilized significantly differ from one another. The findings of the SPT test were used to conduct the analysis of bearing capacity. In this work, drill piles with a 1 m diameter and 15 m depth were used. According to the analysis's findings, the permit's bearing capacity using the Reese & Wright approach was 246.20 tons, however the permit's bearing capacity using the Meyerhof method was found to be 541.87 tons. For the Reese & Wright approach, the single drill pile decreased by 9,07 mm, and the group pile decreased by 25,7 mm; for the Meyerhof method, the single drill pile decreased by 9,17 mm, and the group pile decreased by 25,34 mm. Furthermore, it was found from both methods of calculating the bearing capacity that both stable static loads and dynamic loads work so that the foundation can be categorized (P max < Q single permit). The ratio of the bearing capacity of the single mast permit on the Reese & Wright method compared to the Meyerhof method is 0.478:1. Keywords: Bearing Capacity, Drilled Pile, Stability.